2014
DOI: 10.1007/s00438-014-0895-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between the STK15 polymorphisms and risk of cancer: a meta-analysis

Abstract: The previous published data on the association between STK15 F31I and V57I polymorphisms and cancer risk remained controversial. Hence, we performed a meta-analysis to investigate the association between cancer susceptibility and STK15 F31I (42,315 cases and 50,542 controls from 62 studies) and V57I polymorphisms (12,891 cases and 17,391 controls from 18 studies) in different inheritance models. Overall, significant association was observed between F31I and cancer risk when all the eligible studies were pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Our results showed that subjects with Phe/Ile genotype or at least one Phe allele had a significant reduced risk to breast cancer in Malaysian Chinese women even after Bonferroni correction, suggesting that it can be act as a strong protective biomarker for breast cancer in the population. This finding was similar to recent meta-analysis studies claiming that the Ile allele was an increase risk factor for breast cancer (Qin et al, 2013;Tang et al, 2013;Dai et al, 2014;Guo et al, 2014;Xu et al, 2014;Qin et al, 2015). In Malaysia, Malaysian Chinese women has the highest breast cancer incidences when compared to other ethnic groups (Leong et al, 2007;Pathy et al, 2011), and it is yet to clarify that the role of genetic abnormality contribute to the high incidence rate in this ethnic.…”
Section: 647 Association Of Cyp2e1 Stk15 and Xrcc1 Polymorphisms Wisupporting
confidence: 76%
See 1 more Smart Citation
“…Our results showed that subjects with Phe/Ile genotype or at least one Phe allele had a significant reduced risk to breast cancer in Malaysian Chinese women even after Bonferroni correction, suggesting that it can be act as a strong protective biomarker for breast cancer in the population. This finding was similar to recent meta-analysis studies claiming that the Ile allele was an increase risk factor for breast cancer (Qin et al, 2013;Tang et al, 2013;Dai et al, 2014;Guo et al, 2014;Xu et al, 2014;Qin et al, 2015). In Malaysia, Malaysian Chinese women has the highest breast cancer incidences when compared to other ethnic groups (Leong et al, 2007;Pathy et al, 2011), and it is yet to clarify that the role of genetic abnormality contribute to the high incidence rate in this ethnic.…”
Section: 647 Association Of Cyp2e1 Stk15 and Xrcc1 Polymorphisms Wisupporting
confidence: 76%
“…Taken together, there is significant evidence showing that these three genes are involve in modulating the pathway in the development of breast cancer. Single nucleotide polymorphisms (SNPs) in CYP2E1 (rs6413432 and rs3813867), STK15 (rs2273535 and rs1047972) and XRCC1 (rs1799782 and rs25487) were inconclusively associated to breast cancer risk in case-control or meta-analysis studies in different populations (Wu et al, 2006;Bu et al, 2014;Dai et al, 2014;Ding et al, 2014;Feng et al, 2014;Guo et al, 2014;Qin et al, 2015), but association of these SNPs to breast cancer in Southeast Asia populations, especially in Malaysian women was unquestionably insufficient. Therefore, this pilot study investigates the association of these SNPs, together with etiology factors such as age and ethnicity, to breast cancer risk in Malaysian women.…”
Section: Introductionmentioning
confidence: 99%
“…However, it might be important for kinases activity as the 57Ile homozygote genotype has 57.5% less kinases activity and showed more chromosome instability than the 57Val homozygote genotype (Dogan et al 2008). These two SNPs are associated independently with both sporadic and hereditary cancers, especially in gastrointestinal cancer (GIC) including esophageal, gastric, pancreas, and colorectal as well as other cancers such as breast, ovarian and lung through case-control or metaanalysis studies in different populations (Chen et al 2014(Chen et al , 2007Chong et al 2016;Dai et al 2014;Ju et al 2006;Kimura et al 2005;Qin et al 2015;Tang et al 2013;Xu et al 2014). We have previously reported that carriers with at least one copy of the c2 allele in the CYP2E1 gene was associated to GIC in Malaysians (Chong et al 2014), but the association of the Phe31Ile and Val57Ile SNPs in STK15 to GIC in the population is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…AURKA polymorphisms have been proved by many studies to be the genetic factors of disrupting the centrosome functions [20]. Results of previous studies are different and this may be due to different races, tumours and sample sizes of the studies [21,22]. Our study researched the association of AURKA gene T91A and G169A polymorphisms with oral cancer risk.…”
Section: Discussionmentioning
confidence: 96%